Desain Alat Uji Impak Struktur Las Gesek Bar-Plate Menggunakan Bantuan Computer Aided Engineering (CAE) - Jery Indra Putra Harianja; Yohanes Yohanes; Muftil Badri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Friction Welding is one of the well known press welding methods, where the method is joining two pieces of metal materials. By in this method the heat resulted from the change in mechanical energy into thermal energy in the field of interface the workpiece due to friction during motion plays under pressure/friction. Rotaryfriction welding is made from bar-plate specimens and its products tested by tensile test but not optimal because the weld test objects attached again by adding one bar on the other side, so that acquired way of knowing the characteristics of friction welding the connection using the impact test, so it required the design and manufacture of tools the impact test that aims to get the construction design and the impact tester of friction welding structure of bar-plate. Construction design includes chassis, axle, fixture, and a disc Binder then simulated using ANSYS to view voltage that occurs in the design does exceed the allowed voltage. The component designer is simulated order and the fixture result States that voltage happens during testing does not exceed the allowed limits, it is stated that decent design is created. Impact tester created then tested, and the results stated that no failure occurred on the tools in the form of a broken or cracked, so the impact tester that are worth to be used.Key words: Friction Welding, Bar-plate, Design, Impact Tester, ANSYS